Neighborhood Association, Peer Communication, and Self-Assistance Behaviors Against Disaster Among Individuals With Spinal Cord Injury. (26th August 2023) - Takahashi, Kyo
Abstract: Objective: Individuals with spinal cord injuries (SCIs) are vulnerable in case of disaster, and it is unknown how they can prepare themselves for such events. This study explored factors associated with self-assistance behaviors against disasters. Methods: An internet-based cross-sectional survey was conducted in Japan. The participants were 70 individuals with SCI in a self-help group in Japan. Self-assistance behaviors against disaster were defined in terms of personal network, escape, information, essential items, disaster drill participation, and list registration. After identifying significant variables through binary analyses, logistic regression analysis was conducted to adjust for age and sex. Results: Neighborhood association and peer communication significantly predicted list registration (AOR:2.97; 95% CI:1.05 – 8.40; P = 0.04; AOR:2.79, 95% CI:1.00–7.74, P = 0.05). However, no significant factor was found in relation to other self-assistance behaviors against disasters. Conclusion: Belonging to a neighborhood association and having communication with peers could help individuals with SCI register on a list for assistance during disaster. To promote self-assistance behaviors against disasters, access to neighborhood associations, and opportunities for peer communication should be increased.